2022
DOI: 10.1038/s41419-022-05391-7
|View full text |Cite
|
Sign up to set email alerts
|

FMR1 promotes the progression of colorectal cancer cell by stabilizing EGFR mRNA in an m6A-dependent manner

Abstract: FMR1, a new m6A reader, is known to be involved in the regulation of cancer progression. However, its role, regulatory mechanism, and clinical significance in colorectal cancer (CRC) are elusive. Here, we showed that FMR1 was upregulated in CRC, and it promoted proliferation and metastasis of CRC cells in vitro and in vivo. Mechanically, FMR1 recognized the m6A-modification site in EGFR mRNA, a key molecule in cancer occurrence and targeted therapy, sustained its stability and maintained its expression in an m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Fragile X mental retardation 1 (FMR1) has been identified as a new immune-related prognostic biomarker for renal clear cell carcinoma (Wu et al 2022 ). In addition, FMR1 can promote the development of colorectal cancer cells by stabilizing EGFR mRNA (Hu et al 2022 ). Studies have shown that FMR1 is closely related to the prognosis of various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Fragile X mental retardation 1 (FMR1) has been identified as a new immune-related prognostic biomarker for renal clear cell carcinoma (Wu et al 2022 ). In addition, FMR1 can promote the development of colorectal cancer cells by stabilizing EGFR mRNA (Hu et al 2022 ). Studies have shown that FMR1 is closely related to the prognosis of various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether hnRNPA2B1 promotes CRC cell proliferation in an m6A-dependent manner or not has not been elucidated. FMR1, a new m6A reader, is known to recognize the m6A-modification site in EGFR mRNA, sustain its stability, and maintain its expression in an m6Adependent manner, thereby prohibiting apoptosis and promoting the cell-cycle progression of CRC cells (87).…”
Section: Other "Readers" In Crcmentioning
confidence: 99%
“…The overexpression of IGF2BP2 promotes TFRC expression and facilitates the metabolism of iron in accelerating CRC malignancy [19] . Noteworthy, through m6A-dependent mechanism, FMR1 upregulates the stability of EGFR to enhance the tumorigenesis in colorectal cancer [20] . TNF-α upregulates USP14 expression that is vital for increasing JNK levels and developing feedback loop in promoting tumorigenesis [21] .…”
Section: Introductionmentioning
confidence: 99%